2014
DOI: 10.1007/s10658-014-0518-2
|View full text |Cite
|
Sign up to set email alerts
|

Host ranges of Potato spindle tuber viroid, Tomato chlorotic dwarf viroid, Tomato apical stunt viroid, and Columnea latent viroid in horticultural plants

Abstract: Host ranges of Potato spindle tuber viroid (PSTVd), Tomato chlorotic dwarf viroid (TCDVd), Tomato apical stunt viroid (TASVd), and Colmunea latent viroid (CLVd) were investigated in 30 species from 12 genera of horticultural plants that are frequently traded internationally. They were mechanically inoculated, and viroid infection was checked using both ways of reverse-transcription polymerase chain reaction and back-inoculation to tomato. Among 30 species examined, eight to 10 were susceptible to PSTVd, TCDVd,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 30 publications
1
7
0
2
Order By: Relevance
“…This is in agreement with previous reports that PSTVd isolates differentially infected cultivars of tomato and potato (Hammond and Zhao 2000;Owens and Hammond 2009;Sano et al 1992). The findings that (i) few plant species tested developed symptoms following inoculation with these viroids (e.g., only a single tomato cultivar in the present study) and (ii) symptomless infections were detected in other species (various solanaceous species in the present study) are in agreement with previous studies of the host range of PSTVd and TASVd and further show the complexity of the viroid-host interaction (Diener 2003;Ding 2009;Flores et al 2005Flores et al , 2014Hull 2013;Matsushita and Tsuda 2015;Navarro et al 2012;Tabler and Tsagris 2004). Furthermore, although the host range studies of PSTVd and TASVd conducted by Matsushita and Tsuda (2015) and in the present study are difficult to compare directly because of focusing on plant species commonly imported into Japan versus indicator plants and agricultural plants, respectively, both studies revealed few species that developed symptoms but a relatively broad host range when symptomless hosts were included.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with previous reports that PSTVd isolates differentially infected cultivars of tomato and potato (Hammond and Zhao 2000;Owens and Hammond 2009;Sano et al 1992). The findings that (i) few plant species tested developed symptoms following inoculation with these viroids (e.g., only a single tomato cultivar in the present study) and (ii) symptomless infections were detected in other species (various solanaceous species in the present study) are in agreement with previous studies of the host range of PSTVd and TASVd and further show the complexity of the viroid-host interaction (Diener 2003;Ding 2009;Flores et al 2005Flores et al , 2014Hull 2013;Matsushita and Tsuda 2015;Navarro et al 2012;Tabler and Tsagris 2004). Furthermore, although the host range studies of PSTVd and TASVd conducted by Matsushita and Tsuda (2015) and in the present study are difficult to compare directly because of focusing on plant species commonly imported into Japan versus indicator plants and agricultural plants, respectively, both studies revealed few species that developed symptoms but a relatively broad host range when symptomless hosts were included.…”
Section: Discussionsupporting
confidence: 92%
“…Disease symptoms induced by viroids range from extremely severe (e.g., stunting, shortened internodes, and distorted growth; epinasty, crumpling, and chlorosis of leaves; and necrosis of leaf veins, petioles, and stems) to mild or no symptoms (e.g., symptomless infections in many ornamental plants). Symptomless hosts complicate viroid detection and host range determination, and may serve as reservoirs for infection of economically important crops (Bar-Joseph 2003;De la Peña and Flores 2002;Fadda et al 2003;Matsushita and Tsuda 2015;Murcia et al 2011;Singh et al 1992;Spieker 1996;Verhoeven et al 2015). The mechanisms underlying the wide range of symptoms induced in plants infected by viroids are not well understood but may involve viroid-induced posttranscriptional gene silencing of host genes (Adkar-Purushothama et al 2015;Pallas et al 2012).…”
mentioning
confidence: 99%
“…While this indicates that the economic damage caused by TCDVd infection in eggplant crops is null or insignificant, the lack of symptoms also facilitates that eggplant crops act as undetected sources of infection and reservoirs of TCDVd (Verhoeven et al, 2017). On the other hand, Matsushita & Tsuda (2015) found that eggplant plantlets artificially inoculated with TCDVd, as well as with PSTVd, tomato apical stunt viroid (TASVd), and columnea latent viroid (CLVd), presented intermittent necrosis on leaf veins after inoculation. This may suggest that this was a specific response of the eggplant genotype they used when artificially inoculated with pospiviroids.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, family Pospiviroidae with five genera has PSTVd-like members, consisting of five major domains as secondary structures, asymmetric rolling-circle replication that occurs in the nucleus and are commonly devoid of any ribozyme activities. Avsunviroidae infect only dicotyledonous plants, both herbaceous and woody [ 20 ] while viroids of the family Pospiviroidae can infect both monocot and dicot plants [ 64 ].…”
Section: Taxonomy and Classification Of Viroidsmentioning
confidence: 99%